Environment and Settlement: Ørland 600 BC - AD 1250: Archaeological Excavations at Vik, Ørland Main Air Base (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"During the Late Bronze Age, the Iron Age and early medieval period (c. 600 BC–AD 1250) settlement at Vik in the Ørland peninsula emerged, flourished, vanished and emerged anew. Local landscape and vegetation development, cross-regional cultural developments and global climatic events were of great significance to the farmer-fisher communities at Vik throughout these periods. In this book, results from the 2014–2016 archaeological excavations at Ørland main air base have been refined and developed. The 13 papers deal with landscape, vegetation and environmental aspects related to the excavated settlement, as well as the spatial and social organization of the built environment. Building traditions, disposal practices, the form and representation of everyday objects, subsistence and landscape use are central to the discussions."